Evaluation of soybean (Glycine max) genotypes for seed longevity - KUCHLAN, P; HUSAIN, S M; CHAUHAN, G S (The Indian Journal of Agricultural Sciences, 2011)
Variability in seed quality traits associated with seed longevity was studied during 2005 for 15 soybean (Glycine max (L.) Merrill) cultivars of 3 different seed sizes, small (‘ADT1’, ‘Co1’, ‘Indira Soya 9’, ‘MAUS 32’ and ‘JS 90-41’), medium (‘JS 335’, ‘JS 71-05’, ‘MAUS 47’, ‘NRC 37’ and ‘Bragg’) and bold type (‘JS 9305’, ‘NRC 7’, ‘PS 1024’, ‘PS 1029’ and ‘MAUS 61-2’) under accelerated ageing condition at 90% relative humidity and 42°C temperature. Soil emergence, seed coat rupture force, water imbibition kinetics, reduction in germination due to stress were observed because these are directly or indirectly related with seed longevity characteristics. Faster decline in seed germination after aging at high temperature and humidity was observed in ‘Co 1’, which absorbed more moisture and required less rupture force to break the seed coat. Significantly high positive correlation coefficient, (r=0.766**) was found between soil emergence and germination after 8 days of accelerated ageing.